2021
DOI: 10.1186/s12877-021-02610-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between change in handgrip strength and cognitive function in Korean adults: a longitudinal panel study

Abstract: Background Muscular function, such as handgrip strength, has been suggested as an associated factor for cognitive impairment. This study investigated the association between temporal change in handgrip strength and cognitive function using longitudinal, nationwide data from Korean older adults. Methods Our study used data from the Korean Longitudinal Study of Aging (KLoSA). The analysis covered 6696 participants who had taken the handgrip strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
(41 reference statements)
5
11
0
Order By: Relevance
“…73 A shred of literature identified that HGS is related to several health conditions. 70,[74][75][76] Our findings are similar to the results from previous studies suggesting that the presence of common mechanisms shared by muscle loss and cognitive declines such as chronic conditions and physical activity were potential risk factors that precede future cognitive dysfunction and weaker HGS. 69,70 Limiting physical activity reflects on HGS, resulting in reduced cognitive function of older individuals.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…73 A shred of literature identified that HGS is related to several health conditions. 70,[74][75][76] Our findings are similar to the results from previous studies suggesting that the presence of common mechanisms shared by muscle loss and cognitive declines such as chronic conditions and physical activity were potential risk factors that precede future cognitive dysfunction and weaker HGS. 69,70 Limiting physical activity reflects on HGS, resulting in reduced cognitive function of older individuals.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are similar to the results from previous studies suggesting that the presence of common mechanisms shared by muscle loss and cognitive declines such as chronic conditions and physical activity were potential risk factors that precede future cognitive dysfunction and weaker HGS 69,70 . Limiting physical activity reflects on HGS, resulting in reduced cognitive function of older individuals 75 . The incidence of physical frailty could be another explanation for the relationship between HGS and cognitive impairment 22,74 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, the SARC-F score may not have the same predictive value for subsequent cognitive function decline compared with handgrip strength dynamometry. Longitudinal associations have been found between handgrip strength and cognitive functioning decline in previous studies [ 28 30 ], and our results showed that lower handgrip strength at baseline was associated with subsequent development of cognitive impairment in 1 year. We did not find a similar longitudinal association between the baseline SARC-F score and cognitive impairment at follow-up.…”
Section: Discussionsupporting
confidence: 80%